Evolution, genetics and biochemistry of plant cannabinoid synthesis: a challenge for biotechnology in the years ahead. (June 2022) - Melzer, Rainer; McCabe, Paul F; Schilling, Susanne
Graphical abstract: Abstract : Cannabis sativa is most prominent for its psychoactive secondary compound tetrahydrocannabinol, or THC. However, THC is only one of many phytocannabinoids found in this (in)famous medicinal plant. The stepwise legalization of Cannabis in many countries has opened opportunities for its medicinal and commercial use, sparking scientific interest in the genetics and biochemistry of phytocannabinoid synthesis. Advances in plant biology and genomics help to accelerate research in the Cannabis field, which is still lagging behind other comparable high-value crops. Here, we discuss the intriguing genetics and evolutionary history of phytocannabinoid synthases, and also show that an increased understanding of Cannabis developmental genetics and morphology are of critical importance to leverage the full potential of phytocannabinoid production.